Knowledge and practice of biosafety in the students of the VI regular cycle of the Roosevelt Huancayo University 2022 - Quinto Allca , Edit Nilba (2023)
Objective: To determine the relationship between the level of knowledge and practice of biosafety in students of the VI regular cycle of the university Roosevelt Huancayo 2022. Material and Methods: The type of research was basic non-experimental, descriptive correlational cross-sectional design. The population consisted of 49 students of the VI regular cycle of the Universidad Franklin Roosevelt 2022, the sample was found by non-probabilistic sampling and consisted of the entire population, the technique was the survey and the instrument was the questionnaire. Results: In response to the general objective, out of 49 students of the VI regular cycle of the Roosevelt University of Huancayo, 20 (40.8%) had a low level of knowledge about biosafety, of which 6 (12.2%) had poor biosafety practices, 2 (4.1%) had regular practices and 12 (24.5%) had good biosafety practices. On the otherhand, 27 (55.1%) of the students had an average level of biosafety knowledge, of which 6 (12.2%) developed bad biosafety practices, 1 (2.0%) regular practices and 20 (40.8%) good practices. And of the total of only two students (4.1%) presented a high level of biosafety knowledge who present bad biosafety practices. Conclusion: It was determined that there is no significant relationship between the knowledge and practice of biosafety in the students of the VI regular cycle of the Roosevelt University of Huancayo 2022. The p-value (sig.=0.495) was greater than the significance level (α=0.05).